Recommendations on COVID‐19 triage: international comparison and ethical analysis - Jöbges, Susanne; Vinay, Rasita; Luyckx, Valerie A.; Biller‐Andorno, Nikola (Bioethics, 2020)
On March 11, 2020 the World Health Organization classified COVID‐19, caused by Sars‐CoV‐2, as a pandemic. Although not much was known about the new virus, the first outbreaks in China and Italy showed that potentially a large number of people worldwide could fall critically ill in a short period of time. A shortage of ventilators and intensive care resources was expected in many countries, leading to concerns about restrictions of medical care and preventable deaths. In order to be prepared for this challenging situation, national triage guidance has been developed or adapted from former influenza pandemic guidelines in an increasing number of countries over the past few months. In this article, we provide a comparative analysis of triage recommendations from selected national and international professional societies, including Australia/New Zealand, Belgium, Canada, Germany, Great Britain, Italy, Pakistan, South Africa, Switzerland, the United States, and the International Society of Critical Care Medicine. We describe areas of consensus, including the importance of prognosis, patient will, transparency of the decision‐making process, and psychosocial support for staff, as well as the role of justice and benefit maximization as core principles. We then probe areas of disagreement, such as the role of survival versus outcome, long‐term versus short‐term prognosis, the use of age and comorbidities as triage criteria, priority groups and potential tiebreakers such as ‘lottery’ or ‘first come, first served’. Having explored a number of tensions in current guidance, we conclude with a suggestion for framework conditions that are clear, consistent and implementable. This analysis is intended to advance the ongoing debate regarding the fair allocation of limited resources and may be relevant for future policy‐making.